The Ties That Bind: Linkages Among Secondary Schools, Two-Year Colleges And Baccalaureate Institutions - Lorence, James (Teaching History: A Journal of Methods, 1995)
The University of Wisconsin Center-Marathon County in Wausau is a two-year transfer institution that is a fully-integrated unit in the University of Wisconsin System. Center students may complete the first two years of the baccalaureate program and suooessfu1ly transfer their freshman-sophomore course work to any four-year institution in the state. Most of the thirteen two-year centers in this system are located in the outlying areas of the state, which means their student bodies are often homogeneous in composition. though in part non-traditional. As an~ access institution, the university center must often serve the needs of students whose basic skills are either poorly-developed or rusty after years outside the academic life. Simultaneously, UW Center faculties must also challenge some of the brightest students produced by the secondary schools of outstate Wisconsin. Because of their close ties with their host communities, Wisconsin's two-year institutions are uniquely situated to function as community resources in every sense of the word.